Avatars of Whiteness: Racial Expression in Video Game Characters - Dietrich, David R. (Sociological Inquiry, 2013)
Video games are an enormous segment of popular media today, comparable to tele-vision and movies. Moreover, video games represent a new form of media distinguishedfrom previous forms due to the interactive element, where game players have the ability to change and influence the game world. This paper contributes to the study of race and popular media by examining how race is presented in role-playing video games throughthe feature of avatar creation. Capabilities for avatar creation are analyzed in over sixty massively multiplayer online role-playing games (MMORPGs) in service as of early2010 and twenty offline role-playing games (RPGs) published over the past 10 years.The analysis shows that the vast majority of games, both online and offline, do not allow for the creation of avatars with a non-white racial appearance. Forcing an Angloappearance on avatars that purport to represent the player has the potential to reinforce asense of normative whiteness as well as shape the social composition of online worldsinto all-white virtual spaces, contributing to the creation of a virtual“white habitus.”
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé